Conformationally restricted and Bis-aryl guanidinium derivatatives : towards imroved Alpha2-adrenergic affinity and antagonism for the treatment of depression - McMullen, Michael (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
The evident necessity to develop novel therapeutics to treat depression has been recently highlighted by the World Health Organisation who has listed depression to be the second largest global health burden by the year 2020. The heterogeneity of depression implies that multiple neuronal substrates and mechanisms contribute to its aetiology, making therapeutic research advancements in this area extremely difficult. Pharmacological manipulation of monoamine transmission constitutes the mechanism of all clinical antidepressants through the normalisation of chemical levels and hence the alleviation of depressive symptoms.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.